ON THE STATUS OF THE LINGUISTIC UNIT OF THE PHRASEME (Scientific journal of the Fergana State University, 2023)
This article is devoted to one of the topics - the status of the phrase as a linguistic unit, which is the reason for discussion by groups of scientists for many years, the scientific and theoretical opinions of linguists are analyzed, proving that words, as components of a phrase, either lose their lexical status, or participate in the formation of phrases maintaining the quality of the components, and examples are given. In the phraseological stock of each language, various expressions are formed from a semantic point of view, the views of representatives of the new direction are given.